Unfair - Ett actionorienterat 2D-plattformsspel skapat i Unity Personal - Hallin, Anton; Larsson, Maria; Magnusson, Johannes; Ståhlsparre, Henrik; Åkesson, Mattias (My University, 2015)
Over the past decades the gaming entertainment market has been growing steadily and is showing no signs of discontinuing this trend. With expanding target demographics and increased gaming prescence all over the world it is safe to say it has become a signi cant actor on the global economical market. This thesis aimed to answer the question: How can game mechanics for a 2D action platform game be implemented in the development platform Unity Personal. This is accomplished by performing a study in game design and Unity based game development, and using the results of these to create and implement a game. The result is a prototype of a simple 2D platformer with examples of implementation methods for a number of game mechanics. What became the most important learned experience from this project is the intricacy of the game development process. Many missteps can be made in both the planning and execution of such a process, some of which will be elucidated in this paper.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology